PEMBUATAN GAME ARCADE-STYLE RACING “CARSTIME” DENGAN TEMA ANTIGRAVITASI BERBASIS ANDROID - Michael Michael; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This game is made using Unity3D game engine with C# programming language. This game is developed for Android platform. In this game, player will race against bots on track that is not bound by gravity so each car can move even on upside down track. There are three cars that can be used by players, namely C.car, Sonic and Magnum. There are three stages, namely. Map Aspal which doesn’t have any additional difficulties, Map Pasir which makes player’s car move slower and Map Salju which makes player’s car slip. There are three items that player can collect or interact while racing, namely coin which player can collect for buying car, boost can which player can collect to fill boost meter which can be used when full to increase player’s speed for a certain time, and boost pad which will increase player’s and bots speed for certain time when touched. This game is tested by using three methods which are blackbox testing, alpha testing and beta testing. Based on the result, it can be concluded that “CarsTime” has an interesting racing gameplay with hard difficutly on Map Salju and easy difficulty on Map Aspal and Map Pasir